The Impact of Household Waste on Environmental Pollution in Negeri Passo, Baguala District, Ambon City - Barends, Alfredo Jacob; Riry, Johan; Leuwol, Ferdinad Salomo (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
Household waste or garbage comes from daily household activities that do not include feces or specific waste. Household waste can affect environmental pollution through decreased water quality, which will affect the level of health of others. On that basis, the author conducted a study to determine the Impact of Household Waste on Environmental Pollution in Negeri Passo, Baguala District, Ambon City. In this study, using the Qualitative Descriptive Research Type, the data collection techniques are observation, interviews, and documentation. Data analysis techniques researchers obtain data from the field, which are analyzed according to the categories of data collected, namely observation/observation, interviews, and questionnaires. The results of this study indicate that the impact of the waste significantly affects the poor air quality near the waste, which can hurt the surrounding community by creating an unpleasant odor and creating many flies in the area, especially during the rainy season. Meanwhile, based on the results of laboratory tests to determine water quality, it was found that the results of the three water sources tested had very high E-coli. The furthest source (A) was 2.0, the slightly closest source (B) was 6.8, and the closest source (C) was 12.